The Holy Word "Is": Czesław Miłosz and the Poetry of Being. - Markowski, Michał Paweł (Polish Review, 2025)
This article follows Czesław Miłosz's idea of "objective poetry" within its philosophical ramifications and tries to find a way to make all the statements by Miłosz and his commentators on "being" and "existence" coherent. The main problem detected in the vast poetic and discursive work of Miłosz is his insistence on "objective poetry," which, due to his adamant allegiance to the philosophy of forms, never attains its supposed goals. In a surprising twist, Miłosz's approach to poetry, instead of being a praise of being, turns into an elaborated praise of language, situated at the opposite pole of his philosophical dualism.